Green Silver Nanoparticles Synthesised Using Medicinal plant Echinops sp. Root Extract for Antimicrobial Applications - H C Ananda Murthy (Nanochemistry Research, 2020)
Metallic nanoparticles have extraordinary antibacterial property. The silver NPs capped by biomolecules from medicinal plants can be disastrous to pathogens. For the first time, green silver nanoparticles (EcS-Ag NPs) were successfully synthesized from the Ethiopian medicinal plant Echinops sp . The most advanced techniques were employed to characterize the NPs. The presence of absorbance maxima, λmax,at 454 nm confirms the formation of EcS-Ag NPs. The UV-DRS studies revealed the band gap of 2.22 eV for NPs. The role of biomolecules as capping agents for EcS-Ag NPs was authenticated by FT-IR spectra. The presence of 4 sharp peaks in the XRD pattern of NPs confirmed the highly crystalline nature of NPs. The purity of the NPs was corroborated by SEM-EDAX analysis. The mean particle length of NPs was found to be 33.86 nm. In addition, TEM micrographs revealed the presence of EcS-Ag NPs with varieties of nano-sized shapes. TEM-HRTEM-SAED analysis authenticated the presence of silver NPs with interplanar spacing value of 0.2418 nm which conformed to Ag (111) lattice fringes of NPs. The EcS-Ag NPs showed significant synergistic antibacterial effects against S. aureus, E. coli, P. aeruginosa, and E. aerogenes. The uppermost zone of inhibition of 18 mm was found against S. aureus bacteria. EcS-Ag NPs exhibited better antibacterial activities against gram-positive and gram-negative bacteria.